2017
DOI: 10.1128/jvi.01583-16
|View full text |Cite
|
Sign up to set email alerts
|

TIM-1 Promotes Hepatitis C Virus Cell Attachment and Infection

Abstract: Human TIM and TAM family proteins were recently found to serve as phosphatidylserine (PS) receptors which promote infections by many different viruses, including dengue virus, West Nile virus, Ebola virus, Marburg virus, and Zika virus. In the present study, we provide substantial evidence demonstrating that TIM-1 is important for efficient infection by hepatitis C virus (HCV). The knockdown of TIM-1 expression significantly reduced HCV infection but not HCV RNA replication. Likewise, TIM-1 knockout in Huh-7.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
5
27
0
Order By: Relevance
“…However, binding of PS to a PS receptor alone is not sufficient to mediate the HAVCR1-HCV interaction, since mHavcr1 did not enhance HCV infection, suggesting that the HAVCR1 IgV may also interact with other molecules at the virion surface, such as E1E2. Our results are consistent with previous studies showing that the human HAVCR1 (TIM-1) homologs HAVCR2 (also known as TIM-3) and TIM-4, which are also PS receptors, did not enhance HCV infection (26) and indicate that apoptotic mimicry may not be the only mechanism by which HAVCR1 enhances HCV infection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, binding of PS to a PS receptor alone is not sufficient to mediate the HAVCR1-HCV interaction, since mHavcr1 did not enhance HCV infection, suggesting that the HAVCR1 IgV may also interact with other molecules at the virion surface, such as E1E2. Our results are consistent with previous studies showing that the human HAVCR1 (TIM-1) homologs HAVCR2 (also known as TIM-3) and TIM-4, which are also PS receptors, did not enhance HCV infection (26) and indicate that apoptotic mimicry may not be the only mechanism by which HAVCR1 enhances HCV infection.…”
Section: Discussionsupporting
confidence: 93%
“…3E). This requirement for relatively high concentrations of PS-liposomes to achieve inhibition of HCVcc entry is consistent with previously published data on the role of HAVCR-1 (TIM-1) in HCV entry (26). Similarly, treatment of viral particles with a micromolar concentration of annexin V, a cellular protein that binds to PS, partially inhibited HCVcc entry ( Fig.…”
Section: Havcr-1 (Tim-1) Igv Domain Facilitates Hcv Entrysupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, in addition to their role in viral attachment, these host factors have been shown to also contribute to later steps of the viral life cycle, such as post-binding steps [52,53], internalization [54] or replication [55]. Recently, TIM-1/human hepatitis A virus cellular receptor 1 (HAVCR1)/CD365, a phosphatidylserine receptor that serves as a host factor for various Flaviviridae viruses has been identified as an additional factor contributing to HCV attachment via interaction with phosphatidylserine exposed on the HCV envelope [56]. It has been suggested that HCV-TIM-1 interaction may stabilize/enhance viral attachment and promote subsequent interaction with the main entry factors [57].…”
Section: Host Factors Involved In Viral Attachment To the Hepatocyte mentioning
confidence: 99%
“…Given that MDCK cells are still permissive for ZIKV replication 40 , we hypothesized that a more generalized receptor may be contributing to viral adsorption when ZVBM is NAGylated. The association of human AXL with ZIKV adsorption 3133 suggests that viral phosphatidyl serine (PS) may facilitate entry into certain host cells by binding Gas6, which in turn binds AXL, as is seen with multiple viruses 4145 . We pretreated ZIKV strains MR_766 and PRVABC59 with the PS-binding protein Annexin V prior to infection of Vero cell monolayers.…”
Section: Resultsmentioning
confidence: 99%